Avaliação do impacto de políticas públicas em indicadores sociais: turismo e desigualdades nas estâncias de São Paulo - Juliano, Tiago (2015)
Public policies have increasingly recognized tourism as a means of reducing social inequalities, fostered the development of the activity at different scales. Despite the expectations created by these policies, tourism has not yet consolidated effective recognition among different sectors of society in relation to its role in local development agenda. This study assumes that the attenuation of social inequalities should conform an elementary goal of tourism development and it is based on the question of what has been the contribution of tourism public policies to achieve this role. Thus, the study covers the municipalities that received the title of tourist municipalities between the 1990s and 2010. It employs the method of difference in differences as an evaluation tool of public policy, complemented by other techniques of statistical analysis. The study seeks to confront social indicators of municipalities covered by the policy with other municipalities not served by this action, in periods before and after the government intervention. In this context, the results of five different scenarios are presented, conformed from different estimation techniques, groups of municipalities and variables. In addition to the impact estimations, tourism government representatives were interviewed. Briefly, tourist municipalities represent a positive increase in income indicators, although its impact on the reduction of inequality has not been identified. Therefore, it can be inferred that social potential of tourism has not been used as a broader conception of this phenomenon supposes. A set of interpretations for the results obtained is presented and discussed, pointing an extensive range of expectations for the touristic development. Recent reformulations in the normative framework of the tourist municipalities suggested that monitoring the developments of the main tourism policy at state of São Paulo remains necessary. It’s consistent, especially under the stimulus of competition between municipalities that have unequal resources for the promotion of tourism. Therefore, the reflections on what is the role of activity for local development and who are the actors that matter in this process remain while a fundamental task in tourism studies and indicate that social inequalities should be focused.